Mutations in spliceosomal proteins and retina degeneration - Růžičková, Šárka; Staněk, David (RNA biology, 2017)
A majority of human genes contain non-coding intervening sequences - introns that must be precisely excised from the pre-mRNA molecule. This event requires the coordinated action of five major small nuclear ribonucleoprotein particles (snRNPs) along with additional non-snRNP splicing proteins. Introns must be removed with nucleotidal precision, since even a single nucleotide mistake would result in a reading frame shift and production of a non-functional protein. Numerous human inherited diseases are caused by mutations that affect splicing, including mutations in proteins which are directly involved in splicing catalysis. One of the most common hereditary diseases associated with mutations in core splicing proteins is retinitis pigmentosa (RP). So far, mutations in more than 70 genes have been connected to RP. While the majority of mutated genes are expressed specifically in the retina, eight target genes encode for ubiquitous core snRNP proteins (Prpf3, Prpf4, Prpf6, Prpf8, Prpf31, and SNRNP200/Brr2) and splicing factors (RP9 and DHX38). Why mutations in spliceosomal proteins, which are essential in nearly every cell in the body, causes a disease that displays such a tissue-specific phenotype is currently a mystery. In this review, we recapitulate snRNP functions, summarize the missense mutations which are found in spliceosomal proteins as well as their impact on protein functions and discuss specific models which may explain why the retina is sensitive to these mutations.
Keywords: Mutation, Missense; sestřih RNA; RNA Splicing; ribonukleoproteiny malé jaderné; missense mutace; sestřihové faktory; RNA Splicing Factors; Retinitis pigmentosa; prekurzory RNA; Ribonucleoproteins, Small Nuclear; Spliceosomes; Introns; krysa rodu Rattus; spliceozomy; RNA Precursors; introny; Animals; lidé; splicing; Humans; Retinitis Pigmentosa; zvířata; Rats; snRNP; myši; Mice; retinopathia pigmentosa